Identifying Specific Competencies in Upper-secondary School Vietnamese Language and Literature - Can, Nguyen Duc; Tan, Le Thoi (VNU Journal of Science: Education Research; Vol 34 No 1DO - 10.25073/2588-1159/vnuer.4124, 2018)
The article argues that it is anti-pedagogical to understand that the general competencies are those collectively developed by different subjects, while specific competences are those developed by individual subjects (such as foreign language competencies, mathematics competencies, literature competencies). Learning Vietnamese language and literature is to be able to "write essays", but essay is not about taking tests or doing exam questions under different topics but to comprehend-communicate-collaborate-become civilised in the future. Accordingly, the article attempts a deeper analysis that locates specific competences in their harmonic interrelations to achieve the overall educational aim of Vietnamese language and literature at secondary school today.